2011
DOI: 10.1590/s1413-35552011000300007
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre a limitação nas atividades de vida diária (AVD) e o índice BODE em pacientes com doença pulmonar obstrutiva crônica

Abstract: Background: Chronic Obstructive Pulmonary Disease (COPD) is a progressive disease that reduces functional capacity. deteriorating the ability to perform activities of daily living (ADL). A close relationship between morbidity and mortality with functional limitation is observed in patients with COPD. Objectives: To determine if there is a relationship between ADL limitation and the BODE index. which is a predictor of mortality. in patients with moderate to severe COPD. Methods: Thirty-nine patients with COPD G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 35 publications
0
5
0
3
Order By: Relevance
“…In the present study, there was also a negative correlation between LCADL %total and degree of pulmonary obstruction, although there was no association between the LCADL score and distance walked in the 6MWT, probably due to the reduced sample size (type II error) 23 . It has been previously demonstrated that a score over 50% in the LCADL %total scale indicates severe ADL limitations 24 . In the present study, the mean score was 33.3% and, therefore, in spite of severe airflow obstruction, the sample did not show severe ADL limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, there was also a negative correlation between LCADL %total and degree of pulmonary obstruction, although there was no association between the LCADL score and distance walked in the 6MWT, probably due to the reduced sample size (type II error) 23 . It has been previously demonstrated that a score over 50% in the LCADL %total scale indicates severe ADL limitations 24 . In the present study, the mean score was 33.3% and, therefore, in spite of severe airflow obstruction, the sample did not show severe ADL limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there were no statistically significant correlations between VO 2 and HR τ and MRT with BMI and BMI, suggesting that this parameter do not quantify the slowing of VO 2 and HR on-kinetics. Other authors also claim to have found no relationship between BMI and peripheral muscle impairment, exercise capacity, muscle mass, level of physical activity in daily life or limitations in dailylife activities 36,[42][43][44][45][46] . The absence of correlation can be attributed to the low levels of disease severity in the COPD patients studied (nine patients in quartile 1, four patients in quartile 2 and only one patient in quartile 3).…”
Section: Clt Vo 2 On-kinetics Hr On-kineticsmentioning
confidence: 99%
“…It is a questionnaire of 15 items, divided into four domains (self-care, domestic care, leisure and PA), each item was scored from zero to five, with a maximum of 75 points. The higher the value, the greater the limitation in ADL due to dyspnoea [25]. It is possible to obtain a partial score for each domain [26].…”
Section: Instrumentsmentioning
confidence: 99%